Methyl-CpG binding protein 2 functional alterations provide vulnerability to develop behavioral and molecular features of post-traumatic stress disorder in male mice - Cosentino, Livia; Vigli, Daniele; Medici, Vanessa; Flor, Herta; Lucarelli, Marco; Fuso, Andrea; De Filippis, Bianca (Neuropharmacology, 2019)
Post-traumatic stress disorder (PTSD) is a mental disorder characterized by symptoms of persistent anxiety arising after exposure to traumatic events. Stress susceptibility due to a complex interplay between genetic and environmental factors plays a major role in the disease etiology, although biological underpinnings have not been clarified. We hypothesized that aberrant functionality of the methyl-CpG binding protein 2 (MECP2), a master regulator of experience-dependent epigenetic programming, confers susceptibility to develop PTSD-like symptomatology in the aftermath of traumatic events. Transgenic male mice expressing a truncated form of MeCP2 protein (MeCP2-308) were exposed at adulthood to a trauma in the form of high-intensity footshocks. The presence and duration of PTSD-like symptoms were assessed and compared to those of trauma-exposed wild type littermates and MeCP2-308 mice subjected to a mild stressor. The effects of fluoxetine, a prime pharmacological PTSD treatment, on PTSD-like symptomatology were also explored. Trauma-exposed MeCP2-308 mice showed long-lasting hyperresponsiveness to both correct and incorrect predictors of the trauma and persistent increased avoidance of trauma-related cues. Traumatized MeCP2-308 mice also displayed abnormal post-traumatic plasma levels of the stress hormone corticosterone and altered peripheral gene expression mirroring that of PTSD patients. Fluoxetine improved PTSD-like symptoms in trauma-exposed MeCP2-308 mice. These findings provide evidence that MeCP2 dysfunction results in increased susceptibility to develop PTSD-like symptoms after trauma exposure, and identify trauma-exposed MeCP2-308 mice as a new tool to investigate the underpinnings of PTSD vulnerability.
Gesehen am 30.01.2020